Third-hand smoke exposure is associated with abnormal serum melatonin level via hypomethylation of CYP1A2 promoter: Evidence from human and animal studies. (15th May 2021) - Jiang, Wenbo; Wu, Huanyu; Yu, Xinyang; Wang, Yu; Gu, Wenbo; Wei, Wei; Li, Bai; Jiang, XiTao; Wang, Yue; Hou, Wanying; Dong, Qiuying; Yan, Xuemin; et al.
Abstract: This study aimed to examine whether and how third-hand smoke (THS) exposure would influence serum melatonin level. 1083 participants with or without exposure to THS were enrolled. Serum ROS, SOD, GSH-Px, and melatonin were measured by ELISA. Methylation microarrays detection and WGCNA were performed to identify hub methylated-sites. The methylation levels of hub-sites were validated in addtional samples. Moreover, mice were exposed to THS for 6 months mimicking exposure of human and the serum, liver, and pineal were collected. Oxidative stress-related indicators in serum, pineal, and liver were measured by ELISA. The expressions of mRNA and protein and methylation levels of hub-gene discovered in human data were further explored by RT-PCR, western-blot, and TBS. The results showed the participants exposed to THS had lower melatonin-level. 820 differentially methylated sites associated with THS were identified. And the hub-site located on the CYP1A2 promoter was identified, which mediated the association between THS and decreased melatonin-level. Decreased peak of serum melatonin, increased ROS and reduced SOD and GSH-Px in pineal and liver, and elevated CYP1A2 expression in liver was also found in the THS-exposed mice. Hypo-methylation of 7 CPG sites on the CYP1A2 promoter was identified, which accelerated the catabolism of melatonin. Overall, THS exposure is associated with abnormal melatonin catabolism through hypo-methylation of CYP1A2-promoter. Graphical abstract: Image 1 Highlights: We firstly found the association between third-hand smoke and abnormal serum melatonin. We innovatively combine epigenetics with third-hand smoke for differential methylation sites. We firstly identified the hub gene CYP1A2, and animal models were used to study the potential mechanism. Abstract : We innovatively found that THS-exposure is associated with abnormal serum melatonin levels via hypo-methylation of CYP1A2 promoter in cross-sectional and animal studies.